Pengaruh Pemberian Dedak Kasar Fermentasi pada Domba Ekor Tipis Sebagai Bahan Baku Konsentrat - Defelly Tri Nurcahyani; Suci Wulandari; Suluh Nusantoro (Jurnal Ilmu Peternakan Terapan, 2017)
The aims of this study were to determine the effect of fermented rough rice bran on thin tailed sheep on sheep production performance which included feed consumption of dry ingredients feed, weight gain, and feed conversion. This study consisted of two treatments namely, (P0) rough rice brain as a control and fermented rough rice branÂ  (P1). The method used in this research was T-test. The results showed that the rough bran fermentation was not significantly different (P>0.05) in dry matter consumption, body weight gain, and feed conversion. The highest average gain weight was on P1 (142.58 grams/head/day).